Konkurenceschopnost prodejny spotřebního družstva - Tříletá, Šárka (Jihočeská univerzita, 2020)
The purpose of this thesis is to review and compare the overall competitiveness and position of a selected company on the market in a certain area. Individual stores of a consumer cooperative called Coop were chosen for this analysis. They will be compared with the hypermarkets Kaufland, Albert and Lidl. The competitiveness of individual companies is compared in South Bohemia, in Jindřichův Hradec. The first part of this thesis analyzes the theoretical background and basic issues related to the problem of the competitive ability of the store. Based on the theoretical background, analysis is processed, which explains how the store is doing. For the best result, the necessary data are obtained directly from the employees and branch owners. The overall analysis also includes the opinion of customers and their satisfaction with their purchase. After the analysis and evaluation, the practical part suggests measures that can improve the competitive ability of the store.
Competitiveness of a consumer co-operative's store
Keywords: konkurenceschopnost; spotřebitel; obchod; srovnání; spokojenost; rozdíly; competitiveness; consumer; store; comparison; satisfaction; differences